2006
DOI: 10.1111/j.1399-3054.2006.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and localization of zinc during seed development and germination in wheat

Abstract: In a field experiment, the effect of foliar Zn applications on the concentration of Zn in seeds of a bread wheat cultivar (Triticum aestivum L. cv. Balatilla) was studied during different stages of seed development. In addition, a staining method using dithizone (DTZ: diphenyl thiocarbazone) was applied to (1) study the localization of Zn in seeds, (2) follow the remobilization of Zn during germination, and (3) develop a rapid visual Zn screening method for seed and flour samples. In all seed development stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
258
6
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 336 publications
(298 citation statements)
references
References 34 publications
21
258
6
13
Order By: Relevance
“…Also, a number of microprobe studies on element location in grain, including rice (17,18), and other members of the Poaceae grain utilized for food (19)(20)(21) have shown strong localization of cations in the aleurone, with most studies focusing on Zn. These studies also observed similar localization in the germ of Zn and other cations.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a number of microprobe studies on element location in grain, including rice (17,18), and other members of the Poaceae grain utilized for food (19)(20)(21) have shown strong localization of cations in the aleurone, with most studies focusing on Zn. These studies also observed similar localization in the germ of Zn and other cations.…”
Section: Resultsmentioning
confidence: 99%
“…The present results together with those of Phattarakul et al (2012) suggest that promoting the Zn content in vegetative tissues by foliar Zn application results in Zn being available for re-translocation into seeds. One of the reasons for the stimulated transport of Zn into seeds after the flowering stage might be related to significant increases in protein biosynthesis during the early stage of seed formation (Martre et al 2003;Ozturk et al 2006). As discussed by Cakmak et al (2010b), increasing seed protein concentrations creates a sink for Zn, and there is a close positive correlation between seed protein and Zn concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors is the time of foliar Zn application. In the case of wheat it was shown that the highest Zn concentration in seed was achieved when foliar Zn was applied after the flowering stage (Zadok's scale 7; Zadok et al 1974) compared to the applications realized before the flowering stage (Ozturk et al 2006;Cakmak et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Barley endosperm and aleurone in contrast, together contain $70% of the total Fe, but only 7%-8% in the embryo (Duffus and Rosie 1976). Zinc in wheat is predominantly located in the embryo and aleurone parts of the seed (Ozturk et al 2006). The Zn concentration in seeds is particularly high during early seed development (i.e., at milking stage); thereafter, its concentration gradually declines until maturity.…”
Section: B Distribution Of Iron and Zinc In The Seedmentioning
confidence: 98%
“…The Zn concentration in seeds is particularly high during early seed development (i.e., at milking stage); thereafter, its concentration gradually declines until maturity. Using ear culture system (Singh and Jenner 1983;Sharma et al 1995), the stable zinc isotope 70 Zn, and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) technique, Wang et al (2011) detected preferential localization of Zn in the aleurone and embryo, as also observed by Ozturk et al (2006), but found a gradient of 70 Zn concentration between crease vascular tissue, aleurone layer, and endosperm, demonstrating that Zn is distributed within the seed through the crease phloem. This suggests that two barriers of Zn transport into wheat seeds may exist: between the stem tissue rachis and the seed, and between the maternal and filial tissues in the seed.…”
Section: B Distribution Of Iron and Zinc In The Seedmentioning
confidence: 99%